Pemberdayaan UMKM melalui pelatihan manajemen keuangan dan Digital Marketing di Desa padang kedeper Kabupaten Bengkulu Tengah - Levy Oktridarti; Yori Manis Tika; Linda Astuti; Hania Sumarni; Fanro; Heni Indriani; Imron Rosyadi (JURNAL BESEMAH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in employment creation and community welfare improvement. However, many MSMEs still face challenges in financial management and the utilization of digital technology for marketing purposes. This community service activity aims to enhance the capacity of MSME actors through training in simple financial management and digital marketing. The methods used include socialization, training, mentoring, and evaluation. The results indicate an increase in participants' understanding of business financial recording and their ability to utilize digital media as a marketing tool. Therefore, this program is expected to improve business sustainability and competitiveness of MSMEs in the digital era.